Morphological identification of Glyptothrips species (Thysanoptera: Phlaeothripidae) - Lindner, Mariana Flores; Ferrari, Augusto; Lima, Élison Fabrício Bezerra; Cavalleri, Adriano (Zootaxa, 2023)
Glyptothrips is a New World genus with 14 species of fungivorous Phlaeothripidae found in leaf litter. Identification of species in this genus is difficult due to limited collections of specimens, outdated descriptions, and a lack of keys and images. Here we start addressing these limitations by providing illustrations for each of these species, together with a table of diagnostic characters, and a key to nine species recorded in South America.